The Effect of Human Resource Management Practices (Compensation) on Employee Effectiveness - Rabiu, A.M. (University of Ghana, 2019)
Human Resource Management is the process through which management builds the workforce and tries to create the human performances that the organization needs (Boxall & Purcell, 2016). Compensation which is the ability and responsibility of a company to contribute to its employees for their achievement of task and to appreciate their performance is one of the key HRM activity. This study was conducted to examine the effect of compensation on employee effectiveness. This study examined the influence of compensation on employee effectiveness as well as examined behaviors that employees resort to when they sense compensation inequities. It also determined whether the provision of benefits and incentives have any important effect on employees. The study adopted a quantitative research technique by the use of questionnaires to collect data in achieving the study objectives. A sample size of one hundred and twenty-one (121) employees was used. The study revealed that there is a positive relationship between compensation and employee effectiveness since compensation makes employees committed to the organization and also attracts and motivates qualified employees to perform better and harder. From the study, employees mostly resort to low morale when they sense compensation inequities or go into survival mode and eventually quit when the inequities persist. The study also revealed that providing benefits and incentives to employees reduces employee turnover, promotes the organization’s brand and increased sales leading to increased profits.
MA.
Keywords: Human Resource Management